2000
DOI: 10.1080/026404100446748
|View full text |Cite
|
Sign up to set email alerts
|

A review of batting in men’s cricket

Abstract: In this review, we critically evaluate the scientific research into the morphology and physiology of cricket batsmen. We consider all aspects of the motor control of this skill, in the context of research into dynamic interceptive actions, the biomechanics (kinematics and kinetics) of the various phases of batting strokes and injuries to batsmen. Some attention is also devoted to batting equipment and to psychological factors in batting. Because of the lack of published scientific research into women's cricket… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 54 publications
7
71
1
Order By: Relevance
“…Batting in cricket is a quintessential example of a dynamic interceptive action in sport, and an ideal vehicle for studying interactions between perception and action (Stretch, Bartlett, & Davids, 2000). Ecological psychologists have attempted to describe the control mechanisms involved in regulating movement to satisfy specific task constraints in interceptive actions (e.g., Davids, Renshaw, & Glazier, 2005;Montagne, 2005;Montagne, Cornus, Glize, Quaine, & Laurent, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Batting in cricket is a quintessential example of a dynamic interceptive action in sport, and an ideal vehicle for studying interactions between perception and action (Stretch, Bartlett, & Davids, 2000). Ecological psychologists have attempted to describe the control mechanisms involved in regulating movement to satisfy specific task constraints in interceptive actions (e.g., Davids, Renshaw, & Glazier, 2005;Montagne, 2005;Montagne, Cornus, Glize, Quaine, & Laurent, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The hitting task produced 198 trials that were subsequently digitized using Vicon Motus software (Vicon Motion Systems, U.K.). Following previous research, step length, head-front-knee-foot angle (at contact), head-to-point-of-contact horizontal distance, and bat end point velocity (contact and maximum) were identified as dependent variables (Stretch et al, 2000;Stretch et al, 1998;Woolmer et al, 2008). Data from dependent measures were compared for each bat configuration using a one-way repeated measures analysis of variance (ANOVA) with pairwise comparisons (alpha level <.05).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the front foot drive is used to hit the ball along the ground to minimize the chance of it being caught by a fielder, although the ball can also be lofted with this stroke (Woolmer, Noakes, & Moffett, 2008). Measures such as bat velocity, step length, and body segment angles have all provided insights into how cricket bat-ball interceptive actions are coordinated and have been used to compare successful and unsuccessful performances of shots (Stretch, Bartlett, & Davids, 2000;Stretch et al, 1998;Woolmer et al, 2008).…”
Section: Overview Of Cricket Battingmentioning
confidence: 99%
“…It has recently been shown that the physiological demands of batting in a one-day game are substantial and that players need to be well trained to optimally maintain this type of workload (Noakes & Durandt, 2000;Christie et al, 2011a www.intechopen.com and b). With respect to bowling, although most of the research has focused on lower back injuries (Stretch et al, 2000), it is the view of Noakes & Durandt (2000), that the repeated eccentric actions during fast bowling are the real source of stress for fast bowlers and that this needs to be followed up and related to speed and accuracy of bowling as well as injury potential. Substantial muscle strength is needed to reduce muscle damage arising from these repeated actions (Thompson et al, 1999).…”
Section: Physiological Demands Of Bowlingmentioning
confidence: 99%